ASSESSING THE IMPACT OF BIRTH WEIGHT AND POSTNATAL WEIGHT GAIN ON INSULIN RESISTANCE DURING THE FIRST DECADE OF LIFE. (June 2018) - Lurbe, E.; Torro, I.; Álvarez, J.; Aguilar, F.; Redon, P.; Redon, J.
Abstract : Objective: To assess the impact of birth weight and postnatal weight gain on insulin resistance at 5 and 10 years of life. Design and method: This prospective study, starting at birth, includes 100 subjects born at term. Subjects were divided, according to size at birth, in small, appropriate and large for gestational age. Children were followed up at 5 and 10 years and anthropometric parameters, BP and metabolic parameters (insulin, HOMA index, HDL and Tryglicerides) were obtained. Results: Among the study population, 22 of the children at 10 years old had fasting insulin values higher than or equal to 15U/L, the threshold for defining insulin resistance in the prepubertal stage. Among them, half were overweight and half obese. In the presence of insulin resistance, a clustering of cardiometabolic abnormalities was observed with high values for office SBP (109.0 ± 8.7 vs 102.2 ± 6.5; p < 0.001), log triglycerides (2.1 ± 0.2 vs 1.8 ± 0.2; p < 0.001), uric acid (4.8 ± 0.7 vs 4.0 ± 0.9; p < 0.001), and lower values of HDL (44.1 ± 6.5 vs 56.0 ± 12.5; p < 0.001). In practically all subjects at 5 years that had insulin levels higher than or equal to 15 U/L, these remained high at 10 years. Between 5 years and 10 years, 11 subjects developed insulin resistance, and the main factor related to the incidence of insulin resistance was the presence of obesity (RR 2.6, CI95% 1.3–5.9). The relationship of BW and 5 to 10 year weight gain tertiles with fasting insulin is shown in the Figure. Figure. No caption available. Conclusions: The highest insulin levels, with a clustering of cardiometabolic factors, were observed in those children with the highest weight gain and the lowest BW.